Clinical performance of the Prostate Health Index (PHI) for the prediction of prostate cancer in obese men: data from the PROMEtheuS project, a multicentre European prospective study. (April 2015) - Abrate, Alberto; Lazzeri, Massimo; Lughezzani, Giovanni; Buffi, Nicolòmaria; Bini, Vittorio; Haese, Alexander; de la Taille, Alexandre; McNicholas, Thomas; Redorta, Joan Palou; Gadda, Giulio M.; Lista, Giuliana; Kinzikeeva, Ella; et al.
Abstract : Objectives: To test serum prostate‐specific antigen (PSA) isoform [‐2]proPSA (p2PSA), p2PSA/free PSA (%p2PSA) and Prostate Health Index (PHI) accuracy in predicting prostate cancer in obese men and to test whether PHI is more accurate than PSA in predicting prostate cancer in obese patients. Patients and Methods: The analysis consisted of a nested case‐control study from the pro‐PSA Multicentric European Study (PROMEtheuS) project. The study is registered athttp://www.controlled‐trials.com/ISRCTN04707454 . The primary outcome was to test sensitivity, specificity and accuracy (clinical validity) of serum p2PSA, %p2PSA and PHI, in determining prostate cancer at prostate biopsy in obese men [body mass index (BMI) ≥30 kg/m 2 ], compared with total PSA (tPSA), free PSA (fPSA) and fPSA/tPSA ratio (%fPSA). The number of avoidable prostate biopsies (clinical utility) was also assessed. Multivariable logistic regression models were complemented by predictive accuracy analysis and decision‐curve analysis. Results: Of the 965 patients, 383 (39.7%) were normal weight (BMI <25 kg/m 2 ), 440 (45.6%) were overweight (BMI 25–29.9 kg/m 2 ) and 142 (14.7%) were obese (BMI ≥30 kg/m 2 ). Among obese patients, prostate cancer was found in 65 patients (45.8%), with a higher percentage of Gleason score ≥7 diseases (67.7%). PSA, p2PSA, %p2PSA and PHI were significantly higher, and %fPSA significantly lower in patients with prostate cancer ( P < 0.001). In multivariable logistic regression models, PHI significantly increased accuracy of the base multivariable model by 8.8% ( P = 0.007). At a PHI threshold of 35.7, 46 (32.4%) biopsies could have been avoided. Conclusion: In obese patients, PHI is significantly more accurate than current tests in predicting prostate cancer.